The Phenomenon of An Overqualified Employee: A Review - AjitMurkute, Prachi (International Journal of Psychosocial Rehabilitation, 2020)
A large percentage of the workforce is underqualified or overeducated in comparison to the task they do. This results in a salary disadvantage compared to individuals that are matched appropriately. Several explanations have been offered. An example of this is that overqualification indicates differences in individual skill sets that are unrelated to market need. Another topic is one’s job. Overqualification may be a symptom of a lack of knowledge and a lack of confidence in one’s chosen path. Data from a representative sample is required to determine the degree to which this improvement in career matching is reflected in salary levels. Management practices and research on perceived overqualification are used as an intermediary variable to construct a theoretical model that aims to uncover the "black-box" mechanism of perceived overqualified affecting team performance.